2009
DOI: 10.1016/j.hrthm.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase ζ inhibits Gαq-induced atrial remodeling in transgenic mice

Abstract: BACKGROUND Our previous study demonstrated that diacylglycerol kinase ζ (DGKζ),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Interestingly, overexpression of DGKζ in Gαq-TG hearts inhibited PVC and VT. Our previous study demonstrated that DGKζ restored the prolonged QT interval of ECG (ie, APD prolongation) in Gαq-TG mice. 7 Moreover, DGKζ inhibited atrial and ventricular remodeling and rescued Gαq-induced HF. 5, 7 These results suggest that DGKζ overexpression in the hearts expressing Gαq inhibits ventricular arrhythmias, such as PVC and VT through the improvement of ventricular remodeling such as APD prolongation.…”
Section: Dgkζ-induced Protection Of Ventricular Arrhythmias In Gαq-tgmentioning
confidence: 99%
See 4 more Smart Citations
“…Interestingly, overexpression of DGKζ in Gαq-TG hearts inhibited PVC and VT. Our previous study demonstrated that DGKζ restored the prolonged QT interval of ECG (ie, APD prolongation) in Gαq-TG mice. 7 Moreover, DGKζ inhibited atrial and ventricular remodeling and rescued Gαq-induced HF. 5, 7 These results suggest that DGKζ overexpression in the hearts expressing Gαq inhibits ventricular arrhythmias, such as PVC and VT through the improvement of ventricular remodeling such as APD prolongation.…”
Section: Dgkζ-induced Protection Of Ventricular Arrhythmias In Gαq-tgmentioning
confidence: 99%
“…7 Moreover, DGKζ inhibited atrial and ventricular remodeling and rescued Gαq-induced HF. 5, 7 These results suggest that DGKζ overexpression in the hearts expressing Gαq inhibits ventricular arrhythmias, such as PVC and VT through the improvement of ventricular remodeling such as APD prolongation. Moreover, protein kinase C (PKC) activated by DAG potentiates L-type calcium currents, which increase calcium influx through the channels 20 and inhibits potassium channels, such as the delayed rectifier, 21 suggesting calcium overload in myocardium which leads to triggering events.…”
Section: Dgkζ-induced Protection Of Ventricular Arrhythmias In Gαq-tgmentioning
confidence: 99%
See 3 more Smart Citations